DIFFUSION KINETICS OF PROTON-INDUCED 21NE, 3HE, AND 4HE IN QUARTZ - Shuster D.L.; Farley K.A. (My University, 2005)
A natural quartz sample free of mineral and fluid inclusions was irradiated with a 200 MeV proton beam to produce spallogenic 21Ne, 3He and 4He. Temperature-dependent diffusivities of these three nuclides were then determined simultaneously by high precision stepped-heating and noble gas mass spectrometry. The outward mobility of proton-induced nuclides reflects diffusion through the quartz lattice. In the studied range of 70 to 400°C the helium diffusion coefficients exceed those of neon by 5 7 orders of magnitude. The implied diffusion parameters Ea = 153.7 ± 1.5 (kJ/mol) and ln(Do/a2) = 15.9 ± 0.3 (ln(s-1)) and Ea = 84.5 ± 1.2 (kJ/mol) and ln(Do/a2) = 11.1 ± 0.3 (ln(s-1)) for proton-induced 21Ne and 3He, respectively, indicate that cosmogenic neon will be quantitatively retained in inclusion-free quartz at typical Earth surface temperatures whereas cosmogenic helium will not. However, the neon diffusion parameters also indicate that diffusive loss needs to be considered for small...